3D Branched Ca‐Fe2O3/Fe2O3 Decorated with Pt and Co‐Pi: Improved Charge‐Separation Dynamics and Photoelectrochemical Performance. Issue 14 (26th June 2019) - Chen, Dong; Liu, Zhifeng; Guo, Zhengang; Ruan, Mengnan; Yan, Weiguo
Abstract: The construction of junctions on hematite is an effective way to overcome the problems of slow charge separation and transfer kinetics, but constructing the junction is a significant challenge in photoelectrochemical (PEC) water splitting. Herein, a considerable improvement in PEC performance for α‐Fe2 O3 was achieved following the introduction of a p–n homojunction between n‐type α‐Fe2 O3 and p‐type Ca‐doped α‐Fe2 O3 through a facile hydrothermal method. The resultant 3D branched Ca‐Fe2 O3 /Fe2 O3 enhanced the absorption intensity and reached a photocurrent density of 2.14 mA cm −2 at 1.23 V vs. reversible hydrogen electrode (RHE). The merit of the desired lattice matching of the buried p–n homojunction structure built an internal electric field, which led to appropriate band alignment. These results were supported by a series of photoelectrochemical measurements, in particular, surface photovoltage (SPV) measurements. For further improvement of the charge‐separation efficiency, a combination of separated cocatalysts was established on the homojunction structure, in which Pt acted as the electron collector and was deposited on the bottom, and Co‐Pi as the hole‐extraction cocatalyst was inserted to accelerate hole transfer on the surface of the photoanode. The resulting Co‐Pi/Ca‐Fe2 O3 /Fe2 O3 /Pt branched nanorods showed a significant improvement in charge‐separation efficiency and photocurrent density (2.94 mA cm −2 at 1.23 V vs. RHE). The present strategy, both the construction of the p–n homojunction and the coupling electron‐ and hole‐transfer cocatalyst, could be expanded to many unstable or low‐efficiency semiconductors for the design and fabrication of cost‐effective photoanodes in PEC water splitting. Abstract : Water splitting : The desired lattice matching in a 3D branched Ca‐Fe2 O3 /Fe2 O3 homojunction decorated with spatially separated cocatalysts (Pt and Co‐Pi) can effectively accelerate charge separation and enhance the photoelectrochemical performance of Fe2 O3 . The present strategy may be expanded to many unstable or low‐efficiency semiconductors for the design and fabrication of cost‐effective photoelectrodes.